Osoba dorosła z niepełnosprawnością słuchowa jako odbiorca sztuki (na podstawie wyników badań zrealizowanych na pograniczu pedagogiki specjalnej i neuroestetyki) - Lubińska-Kościółek, Elżbieta; Zielińska, Jolanta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
In this paper the research of art perception by people with hearing disorder has been presented. This study has been performed from the perspective of special pedagogy and neuroesthetic. The encephalography technique and QEEG analysis has been performed with usage of Mitsar-EEG-202 head. This device is controlled by WinEEG software which allows qualitative and quantitative analysis many aspects of EEG signals integrated with two physiological sensors: rhythm of heard and amplitudes of blade pulse and breathing. The results of this study shown usability of the proposed research process for identification new research topics in area of special pedagogy. They also illustrated as many important information about influence of disorder on functioning disable person may be collected by such study. This related in this case to neurological aspects of art perception by by people with hearing disorder.